Effect of Hemodynamic Significant Patent Ductus Arteriosus on Tissue Oxygenation in Preterm Infants using Near-Infrared Spectroscopy. - Martono Tri Utomo, Martono
Abstract Background: Hemodynamic significant Patent Ductus Arterisous (hsPDA) is one of the main complications of preterm birth; however, its management needs further research and development. Ductal stealing results in pulmonary hyperperfusion which potentially causes oxygenation disorders and leads to target organ disruptions (i.e. cerebral, abdominal, and renal). Therefore, monitoring tissue oxygenation is essential for detecting organ disorders. Previous studies revealed that near-infrared spectroscopy (NIRS), as a non-invasive method, showed promising results in monitoring tissue oxygenation. This study aimed to analyze the difference in regional oxygen saturation (rSO2) between premature babies with and without hsPDA. Methods: This cross-sectional study was conducted on preterm infants aged 3-7 days with 24-336/7 weeks of gestation. hsPDA diagnosis was carried out using echocardiography; defined as >1.5 mm diameter of ductus arteriosus and >1.4 left pulmonary artery and aorta (La/Ao) ratio. The cerebral (rcSO2), abdomen (raSO2), and renal oxygen saturation (rrSO2) were measured through NIRS monitoring. The statistical analysis was conducted using SPSS software (Version 21.0). Results: There were 11 out of 52 infants categorized as hsPDA. The mean±SD birth weight, mean±SD gestational age, and mean±SD ductus diameter in hsPDA was determined at 1213±293 gram; 30.72±2.01 weeks, and 2.84±0.93 mm, respectively. There was no significant difference between the hsPDA and non hsPDA groups in terms of rcSO2 (75.27±9.14% and 79.03±9.11%; P=0.238), raSO2 (65.60±11.07% and 67.48±10.17%; P=0.594), and rrSO2 (76.41±14.98% and 82.61±10.41%; P=0.218). Conclusion: Based on the obtained results, the existence of hsPDA doesn't affect the oxygenation in cerebral, abdominal, and renal tissues in preterm babies. Moreover, the decision should be made regarding the optimal time for ductal closure.